The Change of the South Caucasus Regional Securi-ty System and its Impact on the Global Political Processes - Ghevondyan, Robert (ՀՀ ԳԱԱ)
The security systems of the South Caucasus has undergone significant changes due to the 44-day war in Nagorno-Karabakh and subsequent events. The policy of isolating of US president Trump was utilized by regional powers Russia and Turkey for transformations according to their own interests. Russia needed to ensure an alternative transit route for its energy resources before the invasion of Ukraine, while Turkey seized the opportunity to expand his influence in the region. Such a change has not only impacted regional but also global political processes. The Russian-Ukrainian war and the hybrid standoff between Russia and Collective West have found their reflection in the process of reshaping the security system of the South Caucasus. Լեռնային Ղարաբաղում 44-օրյա պատերազմի եւ դրան հաջորդող իրադարձությունների հետեւանքով Հարավային Կովկասի անվտանգային համակարգը ենթարկվեց արմատական փոփոխությունների: ԱՄՆ-ի նախագահ Թրամպի` մեկուսացման քաղաքականությունն օգտագործեցին տարածաշրջանային տերությունները՝ Ռուսաստանը եւ Թուրքիան, ազդեցության գոտիների՝ իրենց շահերին համապատասխան վերաձեւումներ կատարելու համար: Ռուսաստանին անհրաժեշտ էր Ուկրաինա ներխուժելուց առաջ իր էներգակիրների տարանցման համար այլընտրանքային ճանապարհ ապահովել, իսկ Թուրքիան առիթը բաց չթողեց տարածաշրջանում իր ազդեցությունը մեծացնելու համար: Այդ փոփոխությունը մեծ ազդեցություն ունեցավ ոչ միայն տարածաշրջանային, այլեւ գլոբալ քաղաքական գործընթացների վրա: Ռուս-ուկրաինական պատերազմի եւ Ռուսաստան-հավաքական Արեւմուտք հիբրիդային դիմակայության հետեւանքներն արտացոլվեցին նաեւ Հարավային Կովկասի անվտանգային նոր զարգացումներում: Система безопасности Южного Кавказа подверглась серьезным изменениям в результате 44-х дневной войны в Нагорном Карабахе и последующих событий. Политикой изоляции, проводимой президентом США Трампом, воспользовались региональные державы – Россия и Турция. России необходимо было обеспечить альтернативную возможность транзита собственных энергетических ресурсов перед вторжением на территорию Украины, а Турция не упустила возможность расширить собственное влияние в регионе. Это повлияло не только на региональные, но и глобальные политические процессы. Российско-украинская война и гибридное противостояние Россия – коллективный Запад нашли отражение и в процессе переформирования системы безопасности Южного Кавказа.
Keywords: Political science